OPPORTUNITIES CAN BE SEEN AND HEARD DURING THE PANDEMIC: Can you hear me? Can you see me? - Angela Graves (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
This is a commentary article, hence no abstract